Impact of opioid abuse on oral health: a retrospective cohort study - Smeda, Martyna; Knogl, Constanze; Müller, Karolina; Stahl, Martin; Buchalla, Wolfgang; Keim, Lukas; Piendl, Ursula; Wodarz, Norbert; Widbiller, Matthias (Frontiers in Oral Health, 2025)
ObjectivesOpioid use has significantly increased in Germany in recent years. This study aimed to evaluate and compare the oral health, dental hygiene, self-perceived pain, and functional limitations of opioid-addicted patients with a healthy control group.Materials and methods50 opioid-addicted patients (OAP) attending substitution treatment at the Centre for Addiction Medicine of the Department of Psychiatry and Psychotherapy at the University of Regensburg were enrolled and interviewed about their drug use history. A control group was matched for age and sex. The oral health status of patients in both groups was documented using a record of decayed, missing and filled teeth (DMFT), Periodontal Screening Index (PSI), Silness and Loe Plaque Index (PI), stimulated salivary flow rate, buffer capacity and pH. Patients also completed a questionnaire on oral hygiene, functional limitations, dietary habits and other topics. Statistical analysis was performed using non-parametric tests (α = 0.05).ResultsMore men (74%) than women (26%) participated in the study with an age range of 19–64 years. According to the inclusion criteria, all OAP had a history of heroin use, followed by cannabinoids (90%) and cocaine (82%). The median DMFT of the OAP was 21 (IQR = 12–28) and was significantly higher (P < 0.001) than in the control group (median = 10, IQR = 5–16). In addition, the OAP had a significantly higher proportion of periodontal treatment needs (P < 0.001). The PI of the OAP was also significantly worse (P = 0.012). The pH of stimulated saliva from the OAP (median = 6.8, IQR = 6.4–7.2) was significantly lower (P = 0.002) compared to the control group (median = 7.2, IQR = 7.0–7.4). However, there were no significant differences in stimulated salivary flow rate and buffering capacity (P > 0.086). OAP had significantly poorer oral hygiene, with a particular lack of interdental care (P ≤ 0.0012), and a significantly higher consumption of sweets or sweetened drinks appeared to be a problem (P ≤ 0.027). Functional limitations (P < 0.001) were reported to be a burden for OAP.ConclusionOpioid addiction significantly impacts oral health, necessitating improved dental care and confidential treatment services to prevent dental and periodontal diseases and support the social integration of affected individuals.